Evaluation of a managed surgical consultation network in Malawi - Mwapasa, G; Pittalis, C; Clarke, M; Bijlmakers, L; Le, G; Mkandawire, N; Brugha, R; Borgstein, E; Gajewski, J (Springer, 2020)
Background Access to surgery is a challenge for low-income countries like Malawi due to shortages of specialists, especially in rural areas. District hospitals (DH) cater for the immediate surgical needs of rural patients, sending difficult cases to central hospitals (CH), usually with no prior communication.